Hubungan Pengetahuan Tentang Aktivitas Fisik Dengan Tingkat Kecemasan Pada Mahasiswa Dengan Gaya Hidup Sedentari (Sedentary Lifestyle) - Hidayah, Annisa Nurul; Rahmi, Upik; Salasa, Sehabudin (Jurnal Porkes, 2025)
A sedentary lifestyle is a known risk factor for increased anxiety among university students, yet the role of physical activity knowledge in mitigating anxiety remains underexplored. This study aims to examine the relationship between knowledge of physical activity and anxiety levels in students with sedentary lifestyles. Using a quantitative correlational approach with a cross-sectional design, the study involved 80 students aged 19–25 years selected through purposive sampling. Data were collected using a sedentary behavior questionnaire, a validated and reliable physical activity knowledge questionnaire, and the DASS-21 scale to assess anxiety levels. Statistical analysis employed the Chi-Square test. The results revealed that although most students had moderate to high knowledge, over half still experienced moderate to extremely severe anxiety. A significant association was found between physical activity knowledge and anxiety levels (p = 0.000). These findings suggest that knowledge alone is insufficient to reduce anxiety without corresponding behavioral change. Therefore, integrated educational and physical activity programs are essential to promote mental well-being among university students.